DHARAVI‟S CHANGING NATURES - Martha Kolokotroni (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
In an attempt to reach a greater understanding of territorial transformations in slums, this paper discusses in parallel the emergence of touristic activities and the governmental projections for the future of Dharavi; Mumbai’s vibrant settlement. By highlighting the role of mediated images in this process, the project aims to examine the critical perspectives of Dharavi’s changing natures since 2005. Various experiences of Dharavi’s evolution brings into question several levels of under-standing the traditional production of spatial configurations and the findings of this project should not be seen as conclusive but more as starting points.